2016
DOI: 10.1074/jbc.m116.727438
|View full text |Cite
|
Sign up to set email alerts
|

Physical Association of Saccharomyces cerevisiae Polo-like Kinase Cdc5 with Chromosomal Cohesin Facilitates DNA Damage Response

Abstract: At the onset of anaphase, a protease called separase breaks the link between sister chromatids by cleaving the cohesin subunit Scc1. This irreversible step in the cell cycle is promoted by degradation of the separase inhibitor, securin, and polo-like kinase (Plk) 1-dependent phosphorylation of the Scc1 subunit. Plk could recognize substrates through interaction between its phosphopeptide interaction domain, the polo-box domain, and a phosphorylated priming site in the substrate, which has been generated by a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 63 publications
2
20
0
Order By: Relevance
“…Upon Mcd1p-AID depletion, the binding of Cdc5p was abolished genome-wide (Figure 3 and Figure 3-figure supplement 1, Figure 3-figure supplement 2, Figure 3-figure supplement 3), despite similar levels of total Cdc5p(Figure 3-figure supplement 4). This result recapitulated previous work showing the cohesin-dependent binding of Cdc5p at CARs(Mishra et al, 2016;Pakchuen et al, 2016). A few small peaks of binding were observed at centromere and RDN regions, but they coincided with false positives in the GFP-control.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…Upon Mcd1p-AID depletion, the binding of Cdc5p was abolished genome-wide (Figure 3 and Figure 3-figure supplement 1, Figure 3-figure supplement 2, Figure 3-figure supplement 3), despite similar levels of total Cdc5p(Figure 3-figure supplement 4). This result recapitulated previous work showing the cohesin-dependent binding of Cdc5p at CARs(Mishra et al, 2016;Pakchuen et al, 2016). A few small peaks of binding were observed at centromere and RDN regions, but they coincided with false positives in the GFP-control.…”
supporting
confidence: 89%
“…In this study, we provide important clues on how the regulation of condensin by cohesin and Cdc5p is important for the folding of the RDN. First, cohesin is required for the initial recruitment of Cdc5p to chromosomes in mid-M (this study, and (Mishra et al, 2016;Pakchuen et al, 2016)). We showed that cohesin recruitment of Cdc5p to chromosomes promotes Cdc5p binding to neighboring condensin.…”
Section: Cdc5 Recruitment To the Condensin-bound Region Of The Rdn Stmentioning
confidence: 87%
See 3 more Smart Citations